2023
DOI: 10.1055/a-2048-7343
|View full text |Cite
|
Sign up to set email alerts
|

Identifying High-Need Primary Care Patients Using Nursing Knowledge and Machine Learning Methods

Abstract: Background: Patient cohorts generated by machine learning can be enhanced with clinical knowledge to increase translational value and provide a practical approach to patient segmentation based on a mix of medical, behavioral, and social factors. Objectives: To generate a pragmatic example of how machine learning could be used to quickly and meaningfully cohort patients using unsupervised classification methods. Additionally, to demonstrate increased translational value of machine learning models through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Five included studies reveal that nurses implemented AI for patient risk identification. 17 , 21 , 23 , 26 , 27 For instance, a retrospective study by Brom et al utilized CART analysis and electronic health record (EHR) data to identify the risk of readmission in adult patients discharged from medical services. The results showed a 30-day readmission rate of 11.2%, and CART analysis revealed the highest risk for readmission among patients who visited the emergency department, had ≥ 9 comorbidities, were insured through Medicaid, and were ≥ 65 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five included studies reveal that nurses implemented AI for patient risk identification. 17 , 21 , 23 , 26 , 27 For instance, a retrospective study by Brom et al utilized CART analysis and electronic health record (EHR) data to identify the risk of readmission in adult patients discharged from medical services. The results showed a 30-day readmission rate of 11.2%, and CART analysis revealed the highest risk for readmission among patients who visited the emergency department, had ≥ 9 comorbidities, were insured through Medicaid, and were ≥ 65 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Four included studies demonstrate the utilization of AI by nurses to assist in developing nursing care plans. 18 , 20 , 21 , 27 In a discussion paper by Woodnutt et al, ChatGPT was employed to generate a mental health nursing care plan, and its output quality was evaluated against the authors’ clinical experience and existing guidance. The findings indicated that ChatGPT provided a care plan incorporating some principles of dialectical behavior therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedding domain knowledge within ML models can add a layer of interpretability to the model [ 78 ] by providing the rationale behind the model’s recommendations [ 79 ] and allowing the re-traceability of the model decisions to specific model components [ 42 ]. Overall, these integration efforts also increase the transferability of the models and relevance in real-world medical settings [ 80 , 81 ], streamlining their integration into clinical practice. For these reasons, recent advancements in clinical AI focused on developing simpler, more interpretable models made of a minimal set of knowledge-driven features able to provide good explanations [ 50 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the COMPLEXedex-SDH clinical algorithm, cases can be classified into actionable cohorts based on transparent metrics that the nurses can use to identify patients and prioritize interventions, such as outreach calls and cross-sector care alerts, to improve health equity and outcomes. While precision health techniques have been used in recent research to assist in the identification and classification of patients and utilization groups ( Hewner et al, 2023 ), the integration of value-based definitions attempts to capture individuals missed by traditional algorithms, improving reach to individuals disproportionally impacted by SDH.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%